Hemangiopericytoma in Sinonasal Region; A Case Report - M.D., Selçuk Kuzu (International Journal of Innovative Research in Medical Science, 2017)
Hemangiopericytoma is a rare vascular tumor arising from skeletal muscle, although it can originate from any organ system. It is very rare in the sinonasal region. The main treatment is surgical excision. Clinical and radiological findings are not specific. In this case report, a patient with hemangiopericytoma in sinonasal region was described with current literature.